Faecal PCR panel results and clinical findings in Western Australian dogs with diarrhoea. Issue 11 (24th August 2020) - Kim, MW; Sharp, CR; Boyd, CJ; Twomey, LN
Abstract : Aim: To describe faecal PCR (fPCR) results and clinical findings of dogs seen at a university teaching hospital for diarrhoea. Design: Retrospective case series (April 2015 to July 2018). Procedure: Data were collected from the hospital electronic medical records. Data extracted included signalment, history, clinical signs, treatment, fPCR panel results, other faecal diagnostic test results and antimicrobial use. Results: One hundred and sixty‐eight dogs with diarrhoea had a fPCR panel submitted. Most dogs (115, 68.5%) had diarrhoea of 3 days or less duration. Clostridium perfringens alpha toxin gene was most frequently detected (156, 92.9%) by fPCR, followed by Campylobacter spp. (55, 32.7%), canine parvovirus (CPV) (29, 17.3%), Salmonella spp. (14, 8.3%) and Giardia spp. (9, 5.4%). For the 45 dogs that had a negative point‐of‐care CPV test, 13 were CPV fPCR positive; some of which were adult dogs with current vaccination status. A total of 94/168 (56%) dogs received antimicrobials at some time during the treatment of diarrhoea. Conclusion: Faecal PCR panels can identify dogs with enteric organisms in their faeces that traditional faecal diagnostics may miss, thus contributing additional information to the diagnostic process. Nonetheless, fPCR results should be interpreted in light of the clinical findings, and particular consideration given to avoiding inappropriate use of antimicrobials. This study highlights that testing for C. perfringens alpha toxin gene is not likely to be diagnostically helpful, and that adult dogs with diarrhoea might be identified as CPV positive with PCR testing, despite a negative point‐of‐care CPV test result and a current vaccination status.